El tiro por la culata: O las huellas de la transformación de Bogotá (2008)
This article is a meditation on the image of Bogotá and how it has not been able to consolidate as a whole, even though it has improved thanks to the multiple urban and architecturalinterventions it has gone through over the past twenty in order to accommodate the changes of its virulent growth, mostly because the exaltation of an aesthetic of fragmentpromulgated by theoreticians and a continuous tergiversation of urban planning laws from those involved in construction with the solely purpose of individual lucre. This particular conjunction has brought along an urban form that, in opposition to what it looks for, seems more like the outcome of chaos and confusion than the product of any urban intention.